Upaya Peningkatan Pendapatan Asli Daerah melalui Pengembangan Pariwisata di Kabupaten Mamuju - Muh. Taufiq Jaenuddin (Departemen Ilmu Pemerintahan Fisip Unhas, 2019)
This study aims to describe the efforts of the tourism development conducted by the Tourism Office of Mamuju Regency in increasing Income of the original area (PAD) in the Mamuju Regency, as well as to explain the factors that affect the development of tourism in boosting PAD in Mamuju Regency.The research method used is qualitative method with descriptive type. Data collection using literature study techniques, and interviews. Furthermore, the data are analyzed qualitatively.The results of this research show that the efforts made, the first Department of culture and tourism has not been fullest Mamuju Regency in increasing Income of the original area (PAD) through the development of tourism, ranging from promoting tourist attraction, implement the Event and Festival, carry out movements of groups conscious tourism, Tourist Villages, running the program do the increased socialization of human resources both Government related surroundings as well as the community and maintains a presence form cooperation with the Community Manager tourist attraction. Second, the factors that affect Indigenous Areas increased revenue through the development of tourism in Mamuju Regency is a supporting factor, namely the location of the strategic areas and the existence of supporting facilities for tourism, i.e. restricting factors of policy issues, the lack of a budget while the finance, the promotion of the tourist attraction has not been fullest, management of tourist attraction has not been serious, human resources are still limited in scope local governments or community around tourist attraction and there is no local government cooperation with private parties.